2022
DOI: 10.12669/pjms.39.1.6408
|View full text |Cite
|
Sign up to set email alerts
|

Posterior fossa epidural hematoma: A 6-year management experience

Abstract: Objective: Through this study, we sought to evaluate the management of posterior fossa extradural hematoma (PFEDH). Methods: An observational study was conducted at the Neurosurgery Department of Lady Reading Hospital in Peshawar from January 2015 to December 2020. All patients who had a traumatic acute extradural hematoma (EDH) of the posterior fossa were included, irrespective of age and gender. The clinical predictors and outcomes were assessed, including the CT-scan findings and Glasgow Coma Scale (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Observations Sharafat et al, 10 in their 6-year study of 1252 patients with EDH, found 104 patients to have PFEDH, corresponding to approximately 8% of cases. SIEDH is estimated to be a rarer subtype of PFEDH, with an incidence of less than 2% of all EDHs 1 and 11%-70% of all PFEDHs.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Observations Sharafat et al, 10 in their 6-year study of 1252 patients with EDH, found 104 patients to have PFEDH, corresponding to approximately 8% of cases. SIEDH is estimated to be a rarer subtype of PFEDH, with an incidence of less than 2% of all EDHs 1 and 11%-70% of all PFEDHs.…”
Section: Discussionmentioning
confidence: 97%
“…[3][4][5][6][7][8][9] Prognosis can depend on time delay to surgery and presenting Glasgow Coma Scale (GCS) score. 10 Mortality reported in the literature has ranged from 8% to 26%. 10 Supra-and infratentorial epidural hematoma (SIEDH), a rare subtype of PFEDH, occurs in <2% of all EDHs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 The extradural hematomas of the posterior fossa may be categorized as acute or delayed defined with respect to the brain stem compression appearing within or after 24 hours of injury. 3 Surgical evacuation is needed in most of the cases but only few patients can be managed conservatively and some might need surgery later on.…”
Section: Introductionmentioning
confidence: 99%